Endogean and Cavernicolous Coleoptera of the Balkans. XX. Notes on the genus Protamaurops J. Müller, 1944 (Coleoptera: Staphylinidae: Pselaphinae) with the description of a new species from Bulgaria - Bekchiev, Rostislav; Hlaváč, Peter (Zootaxa, 2020)
The genus Protamaurops J. Müller, 1944 and three species: P. macedonicus J. Müller, 1934, P. macrophthalmus J. Müller, 1944 and P. winneguthi Székessy, 1943 are reviewed and redescribed. One new species from Bulgaria, Protamaurops bulgaricus sp. n. is described. Protamaurops montenegrinus (Székessy, 1943) is transferred to the genus Paramaurops Jeannel, 1948 and Protamaurops macrophtalmus beieri (J. Müller, 1944) is synonymized to the nominal species Protamaurops macrophtalmus macrophtalmus (J. Müller, 1944).